Pivot to Telehealth: Narrative Reflections on Circle of Security Parenting Groups during COVID‐19. Issue 1 (27th March 2021) - Cook, Alison; Bragg, Judith; Reay, Rebecca E.
Abstract : In response to COVID‐19 hygiene and physical distancing restrictions, our service rapidly shifted to delivering Circle of Security‐Parenting™ (COS‐P) groups via telehealth. In this article we report the perspectives and experiences of the group facilitator and the parents who received the intervention during the COVID‐19 pandemic. We use semi‐structured, qualitative interviews to explore the advantages, challenges, and positive impacts of the online parenting group from the perspectives of the group leader and the five group participants. Participants' narrative reflections show that they were satisfied with the convenient and engaging online delivery of the program and would recommend it to other parents. Parents reported significant improvements in their parenting and greater awareness of their strengths and struggles. The online delivery of COS‐P resulted in more efficient service delivery, greater attendance rates, and adherence to the model. The stressors on the experienced facilitator, due to the abrupt transition and multiple technical and communication challenges, may have been mitigated by supervisor and collegial support, as well as careful preparation for herself and the participants. Future research should investigate the effectiveness of online versus face‐to‐face delivery of the intervention, including what works for whom.